Kontestasi Partai Persatuan Pembangunan Pada Pemilihan Umum Tahun 2019 - Abdul Rahman; Najamuddin; Wildhan Khalyubi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
The United Development Party (PPP) is one of the contestants in the general election since the new order era until the current Reformation era. In the course of politics in Indonesia, PPP as a party with Islamic nuances has never been the main winner in every election, even though the majority of Muslims in this country. This reaserch aims to reveal about the implementation of the 2019 general election and to elaborate on several events related to the United Development Party (PPP), so that it has an impact on the position of its vote acquisition in the 2019 general election. This study uses a historical qualitative research method. The data was obtained through a study of literature sharing in the form of books and journals. The results showed that PPP set a target to win 8% of the vote at the national level. To achieve this target, PPP has taken several strategies, including: visiting Islamic boarding schools, approaching the millennial generation, introducing new brands, and supporting the Joko Widodo and Ma'ruf Amin couple. However, PPP's hopes of gaining victory could not be realized because it faced several obstacles, namely: PPP's internal divisions, cracking at the ballot box, lack of public figures, and corruption cases. Some of these factors made PPP the party that took the last position in the vote that was declared to have passed as part of the members of the House of Representatives of the Republic of Indonesia.